The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1002/bmc.487
|View full text |Cite
|
Sign up to set email alerts
|

The effects of ligand chain length, salt concentration and temperature on the adsorption of bovine serum albumin onto polypropyleneglycol–Sepharose

Abstract: The interaction thermodynamics associated with bovine serum albumin adsorption on polypropylene glycol (n=3)-Sepharose CL-6B and polypropylene glycol (n=7)-Sepharose CL-6B, using ammonium sulfate as the modulator was studied. Analysis of data under linear conditions was accomplished with the stoichiometric displacement retention model, preferential interaction approach and van't Hoff plots applied to HIC systems. Preferential interaction analysis indicated a strong entropic driving force under linear condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…In general, an analyte with a longer alkyl chain results in a longer retention time because it increases the molecule's hydrophobicity. [26][27][28] The thermodynamic studies are also described for the hydrophobic interaction of polypeptide with nonpolar ligands. 29,30 However, Orlando et al demonstrated the hydrophobic interaction between the self-assembled monolayer of octadecyl mercaptan and octadecanethiol (C 18 ) with polypeptide in the isolation and concentration of analytes for MALDI-MS analysis.…”
mentioning
confidence: 99%
“…In general, an analyte with a longer alkyl chain results in a longer retention time because it increases the molecule's hydrophobicity. [26][27][28] The thermodynamic studies are also described for the hydrophobic interaction of polypeptide with nonpolar ligands. 29,30 However, Orlando et al demonstrated the hydrophobic interaction between the self-assembled monolayer of octadecyl mercaptan and octadecanethiol (C 18 ) with polypeptide in the isolation and concentration of analytes for MALDI-MS analysis.…”
mentioning
confidence: 99%
“…Adsorption of Cyt into the three chromatographic resins is entropically driven. Despite entropically driven adsorption being generally unexpected in ion exchangers, this was reported in the literature for different protein ion-exchangers combinations. ,, Entropic increases are often related to protein structural rearrangements , and, more importantly, the release of water molecules and counterions ,, from the protein and solid-phase surface. The disruption of water structures and the subsequent release of the disordered water molecules to the bulk solution is responsible for the large entropy increases in the ion-exchange processes.…”
Section: Results and Discussionmentioning
confidence: 87%
“…A further benefit of LC over GC is the ability to include conjugates in the analyte profile [22]. Moreover steroids are now an integral part of metabolomics screens [23] e.g. cancer biomarkers.…”
Section: The Art Of Separationmentioning
confidence: 99%